Student teachers' experiences of practical training in a foreign culture. Issue 1 (2nd January 2023) - Koskela, Teija; Granö, Päivi; Somerkoski, Brita
ABSTRACT: Teacher education is usually located in a national context. In this study, the focus is on teacher education located in a foreign studying environment. Student teachers from the southern part of Africa started their teacher education in Finland. The context is their first practicum in Finnish teacher training school. The data consist of one portfolio task of 18 student teachers concerning teaching experiences in a practicum. The content of reflective tasks were analysed based on three dimensions: sensitising, contextual and technical reflection. In addition, the transformation of the teachers' understanding of teaching work was analysed. Despite cultural and linguistic differences, it is possible to find meaningful sensitising, contextual and technical content in reflective tasks. Teachers' understanding of teaching work transformed during their first experience abroad.